Pemanfaatan Koleksi di Perpustakaan Fakultas Pariwisata Universitas Udayana - Surya Permana, I Gusti Agung Bagus; Ginting, Richard Togaranta; Kastawa, Made (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2017)
ABSTRACT The purpose of this study to examine the collections usage at Faculty of Tourism Library, UniversitasUdayana which is expected to support learningandresearch activities. The object of this study are collections which available at Faculty of Tourism Library, UniversitasUdayana. The populations was all students who are members of Faculty of Tourism Library, UniversitasUdayana. Total sample of 86 respondents based on using kredjie-morgan’s table. The research runs from October 2016 until January 2017. Keyword: Collection usage,Library